(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, today one of the most important fruits for our country,not only in the domestic market but also in the export direction, the results of determining the mechanical composition of different varieties of grapes at the beginning and after 4 months of storage, change over time and comparison with each other in the process of harvesting grapes grown in Fergana and Andijan regions of the Republic, their collection from vineyards and storage in modern refrigerated warehouses are showed.